1982
DOI: 10.1128/jb.150.3.1391-1399.1982
|View full text |Cite
|
Sign up to set email alerts
|

Differential metabolism of cellobiose and glucose by Clostridium thermocellum and Clostridium thermohydrosulfuricum

Abstract: Clostridium thermohydrosulfuricum consumed glucose in preference to cellobiose as an energy source for growth. The rates of substrate uptake in glucoseand cellobiose-grown cell suspensions were 45 and 24 nmol/min per mg (dry weight), respectively, at 65°C. The molar growth yields (i.e., grams of cells per mole of glucose equivalents) were similar on cellobiose and glucose (19 and 16, respectively). Both glucose-and cellobiose-grown cells contained a glucose permease activity and high levels of hexokinase (>0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(46 citation statements)
references
References 40 publications
3
42
1
Order By: Relevance
“…In addition to S. rericuli, other cellulose degraders, such as the bacteria Clostridium thermocellum ( Ng and Zeikus, 1982), Ruminococcus fluvefuciens (Helaszek and White, 1991 ), and Thermomonosporu curvuta (Bernier and Stutzenberger, 1987), take up cellobiose. However, neither the biochemical nor the genetic characteristics of these systems have been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to S. rericuli, other cellulose degraders, such as the bacteria Clostridium thermocellum ( Ng and Zeikus, 1982), Ruminococcus fluvefuciens (Helaszek and White, 1991 ), and Thermomonosporu curvuta (Bernier and Stutzenberger, 1987), take up cellobiose. However, neither the biochemical nor the genetic characteristics of these systems have been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…No studies describing the xylobiose transport system have been reported in the literature. Cellobiose transport has been studied in Clostridium thermocellum (Ng and Zeikus, 1982), Thermomonospora curvata (Bernier and Stutzenberger, 1987), Candida wickerhamfi and Clavispora lusitaniae (Freer and Greene, 1990) and Streptococcus bovis (Martin and Russell, 1987). A cellobiose phosphotransferase system has been reported for Bacillus stearothermophilus (Lai and Ingram, 1993) which resembles the system described for Escherichia coli (Hall and Xu, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Sodium-driven transport mechanisms for amino acids have been reported in Clostridium fervidus [14] and Bacillus stearothermophilus [15], but until recently there was little information on the mechanisms of carbohydrate transport by thermophilic bacteria. Thermophiles did not have a PTS for glucose or cellobiose [16][17][18]. Some mesophilic bacteria have facilitated diffusion systems for glucose [19,20], and recent work indicated that T. thermohydrosulfuricus Rt8.B1 had a low affinity glucose uptake system that did not require sodium or a protonmotive force [3].…”
Section: Discussionmentioning
confidence: 99%